Technological Mastery and Competence Development of Islamic Religious Education Teachers in Wonogiri: Supporting SDG 4 on Quality Education - Meti Fatimah; Edy Muslimin; Aminatus Sayidah; Alwy Ahmed Mohamed (Profetika: Jurnal Studi Islam, 2025)
Objective: This research aims to analyse the importance of technology mastery in improving the competence of Islamic Religious Education teachers who are members of the Teacher Working Group Forum to support the achievement of SDG 4. Theoretical Framework: Serves as a conceptual foundation that explains the relationship between mastery of technology, increasing the competence of Islamic Religious Education teachers, and the role of the Teacher Working Group Forum as a forum for developing teacher professionalism. Literature Review: To review various theories and previous research relevant to technology mastery, improving the competence of Islamic Religious Education teachers, and the role of the Teacher Working Group Forum in supporting teacher professional development related to SDG 4. Methods: This study used a qualitative method, the analysis of which involved the content of the technology mastery text, the competence of Islamic Religious Education teachers, and the Teacher Working Group Forum. Data were collected through document analysis and interviews with Islamic Religious Education teachers, the head of the teachers' working group forum, school principals, and policymakers. Results: Islamic Religious Education teachers have a positive perception of technology mastery, as it helps them access more Islamic learning resources, reach a wider range of students, especially in distance learning, and make learning more interactive; in addition, the Teachers Working Group Forum plays a role in helping them learn technology gradually, although there are still challenges such as the lack of technical training, limited technology facilities in schools, the low level of digital literacy of Islamic Religious Education teachers, and concerns about the negative impact of technology use. Implications: In addition, this research contributes to the achievement of the SDGs, particularly in quality education (SDG 4), technological innovation in education (SDG 9), reducing disparities in access to education (SDG 10), and strengthening partnerships in the development of technology-based education (SDG 17). Novelty: Overall, this research brings a new perspective to the field of Islamic religious education by highlighting how mastery of technology can improve the competence of Islamic Religious Education teachers, as well as how the Teacher Working Group Forum can act as a catalyst in digital transformation for religious educators.